Acute renal injury among seriously ill Iraqi children: risk factors, management, and outcome - Matheel Mohammed Jaafer; Nabeeha Najatee Akram; Sahar Basil Hussain; Qasim Rahi Issa (Journal of the Pakistan Medical Association, 2024)
Objectives: To determine the frequency of acute kidney injury in seriously ill young patients, and to find out the risk factors linked to renal impairment. Method: The cross-sectional study was conducted from June 1 to December 1, 2019, at the Central Child Teaching Hospital, Baghdad, Iraq, and comprised patients of either gender aged from >28 days to <18 years who presented to the emergency department with any critical acute illness who had to undergo hospitalisation. Kidney Disease Improving Global Outcomes criterion was used to identify patients having acute kidney injury. Such patients were followed up during their hospitalisation and their follow-up data was collected daily till discharge... Data was analysed using SPSS 25. Results: of the 485 critically ill paediatric patients, 113(23.3%) had acute kidney injury; 57(50.9%) females and 56(49.1%) males. The overall mean age was 18.68±25.8 months (range: 1.5-120 months). There were 46(40.7%) patients with stage 3 disease. The incidence of acute kidney disease was not significantly associated with either age or gender (p>0.05). Diarrhoea and vomiting were the only complaints that had a significant association with acute kidney injury (p=0.001). Sagwa was consumed by 40(8.2%) cases, and 35(87.5%) of them developed acute kidney injury (p=0.001). Ventilator was used in 12(10.6%) cases, Of the total 65(13.4) cases of mortality, 21(18.6%) had acute kidney injury compared to 44(11.8%) of the rest (p=0.014). Conclusion: Acute renal impairment was found to be prevalent in seriously ill paediatric patients and was linked to increased mortality. Sagwa poisoning, diarrhoea and vomiting as presenting complaints had a significant association with acute kidney disease in such patients. Key Words: Critical Illness, Acute Disease, Incidence, Kidney Injury, Ventilators, Diarrhea, Vomiting